2009
DOI: 10.1017/s1461145709990903
|View full text |Cite
|
Sign up to set email alerts
|

Association between autism and variants in the wingless-type MMTV integration site family member 2 ( WNT2) gene

Abstract: Autism is a severe neurodevelopmental disorder with a complex genetic aetiology. The wingless-type MMTV integration site family member 2 (WNT2) gene has been considered as a candidate gene for autism. We conducted a case-control study and followed up with a transmission disequilibrium test (TDT) analysis to confirm replication of the significant results for the first time. We conducted a case-control study of nine single nucleotide polymorphisms (SNPs) within the WNT2 gene in 170 patients with autism and 214 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Program No 58414/E17 2015 Neuroscience Meeting Planner , Chicago, IL: Society for Neuroscience, Online. ) c Iossifov et al, 2014 identified a de novo missense mutation in this gene in a male proband and his unaffected sister (Supplementary Table 2). d Iossifov et al, 2014 identified a de novo missense mutation in this gene in a male proband and his unaffected brother (Supplementary Table 2); Waltes et al, 2014 reported an association between rs25925 of CAMK4 and ASD after genotyping ten SNPs in two sets of German populations. e Iossifov et al, 2014 identified a de novo mutation in an intron of this gene in a male proband and his unaffected sister (Supplementary Table 2). f Pagnamenta et al, 2011 reported rare familial 16q21 microdeletions and expression analyses implicating CDH8 in ASD and ID. g Martin et al, 2013 found a missense variant in WNT1 (S88R) that was overrepresented in ASD patients relative to controls. h Marui et al, 2010 identified three SNPs within WNT2 that showed significant associations with autism. i Neves-Pereira et al, 2009 identified and mapped a de novo chromosome breakpoint between 4q and 5q to an alternative transcript of the gene, as well as two ASD patients with single nucleotide insertions in the EIF4E promoter shown to alter activity. j Barnby et al, 2005 reported a significant association with ASD for SNPs within GRIN2A for rs1014531 and for intron 10. k Iossifov et al, 2014 identified a de novo mutation in an intron of this gene in a male proband and his unaffected sister, and a missense mutation in a female proband and her unaffected sister (Supplementary Table 2). l Laumonnier et al, 2006 identified a breakpoint in this gene in a patient with a de novo translocation, and a second patient with a sequence variation in a highly conserved region of the ion channel encoded by the gene; Neale et al, 2012 identified mutations in this gene in two individual probands, one missense and one silent. m Iossifov et al, 2014 identified a de novo missense mutation of this gene in two male probands and their unaffected sisters, and a synonymous mutation in a third male proband and his unaffected sister (Supplementary Table 2). n Feyder et al, 2010 reported a significant association between variations in two human DLG4 SNPs with neural endophenotypes related to ASD. o Iossifov et al, 2014 identified a de novo mutation in an intron of this gene in a male proband and his unaffected sister, a missense mutation in a male proband and his unaffected sister, and a frame-shift mutation in a male proband and his unaffected brother (Supplementary Table 2). p Benayed et al, 2005 replicated an association between two intronic SNPs in this gene with ASD. …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Program No 58414/E17 2015 Neuroscience Meeting Planner , Chicago, IL: Society for Neuroscience, Online. ) c Iossifov et al, 2014 identified a de novo missense mutation in this gene in a male proband and his unaffected sister (Supplementary Table 2). d Iossifov et al, 2014 identified a de novo missense mutation in this gene in a male proband and his unaffected brother (Supplementary Table 2); Waltes et al, 2014 reported an association between rs25925 of CAMK4 and ASD after genotyping ten SNPs in two sets of German populations. e Iossifov et al, 2014 identified a de novo mutation in an intron of this gene in a male proband and his unaffected sister (Supplementary Table 2). f Pagnamenta et al, 2011 reported rare familial 16q21 microdeletions and expression analyses implicating CDH8 in ASD and ID. g Martin et al, 2013 found a missense variant in WNT1 (S88R) that was overrepresented in ASD patients relative to controls. h Marui et al, 2010 identified three SNPs within WNT2 that showed significant associations with autism. i Neves-Pereira et al, 2009 identified and mapped a de novo chromosome breakpoint between 4q and 5q to an alternative transcript of the gene, as well as two ASD patients with single nucleotide insertions in the EIF4E promoter shown to alter activity. j Barnby et al, 2005 reported a significant association with ASD for SNPs within GRIN2A for rs1014531 and for intron 10. k Iossifov et al, 2014 identified a de novo mutation in an intron of this gene in a male proband and his unaffected sister, and a missense mutation in a female proband and her unaffected sister (Supplementary Table 2). l Laumonnier et al, 2006 identified a breakpoint in this gene in a patient with a de novo translocation, and a second patient with a sequence variation in a highly conserved region of the ion channel encoded by the gene; Neale et al, 2012 identified mutations in this gene in two individual probands, one missense and one silent. m Iossifov et al, 2014 identified a de novo missense mutation of this gene in two male probands and their unaffected sisters, and a synonymous mutation in a third male proband and his unaffected sister (Supplementary Table 2). n Feyder et al, 2010 reported a significant association between variations in two human DLG4 SNPs with neural endophenotypes related to ASD. o Iossifov et al, 2014 identified a de novo mutation in an intron of this gene in a male proband and his unaffected sister, a missense mutation in a male proband and his unaffected sister, and a frame-shift mutation in a male proband and his unaffected brother (Supplementary Table 2). p Benayed et al, 2005 replicated an association between two intronic SNPs in this gene with ASD. …”
Section: Figmentioning
confidence: 99%
“… h Marui et al, 2010 identified three SNPs within WNT2 that showed significant associations with autism. …”
Section: Figmentioning
confidence: 99%
“…The authors identified several variants that segregated with autism and severe language abnormality. Two subsequent linkage studies were not able to confirm the original findings [45,46]; however, a more recent extended study again found an association [47]. This study involved a case–control study of 9 single-nucleotide polymorphisms (SNPs) within the WNT2 gene in 170 autism patients and 214 controls from Japan, and a follow-up of the positive results in a transmission disequilibrium test (TDT) in 98 Japanese autistic family trios.…”
Section: Overview Of Mutations In Wnt Pathway In Patients With Asd (Pmentioning
confidence: 99%
“…This study involved a case–control study of 9 single-nucleotide polymorphisms (SNPs) within the WNT2 gene in 170 autism patients and 214 controls from Japan, and a follow-up of the positive results in a transmission disequilibrium test (TDT) in 98 Japanese autistic family trios. The significant associations from the initial part were replicated in the TDT part and the authors concluded that “ WNT2 is a strong candidate gene for autism” [47]. The function of Wnt2 has also been investigated in laboratory experiments.…”
Section: Overview Of Mutations In Wnt Pathway In Patients With Asd (Pmentioning
confidence: 99%
“…Further studies are suggested for the better understanding of the associations between Wnt gene polymorphisms and BD and their relations with the serotonin signaling [38]. It is of great interest that WNT2 gene is also involved in the etiology of autism [39].…”
Section: Discussion Expression Alterations Of Selected Hub Genesmentioning
confidence: 99%